2022
DOI: 10.3389/fcimb.2022.890750
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Susceptibility to Type I Interferon Response and Subgenomic RNA Accumulation Between Clinical Isolates of Dengue and Zika Virus From Oaxaca Mexico Correlate With Replication Efficiency in Human Cells and Disease Severity

Abstract: Dengue and Zika viruses cocirculate annually in endemic areas of Mexico, causing outbreaks of different magnitude and severity every year, suggesting a continuous selection of Flavivirus variants with variable phenotypes of transmissibility and virulence. To evaluate if Flavivirus variants with different phenotypes cocirculate during outbreaks, we isolated dengue and Zika viruses from blood samples of febrile patients from Oaxaca City during the 2016 and 2019 epidemic years. We compared their replication kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…In addition, inhibition of CHIKV replication was evaluated in human BJ skin fibroblasts (normal cells), since fibroblasts are susceptible to CHIKV infection following mosquito bite. Dermal fibroblasts induce the activation of innate immune responses such as IFNβ secretion, this has been described in HFF-1, HDF cell lines infected with dengue and Zika arboviruses [28][29][30] and in HT-1080 and HS 633T infected with CHIKV [31]. When treated with 100 μM NCAO, a decrease in viral replication was observed at 48 hpi (Figure 7), like what was observed in Vero and C6/36 cells.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, inhibition of CHIKV replication was evaluated in human BJ skin fibroblasts (normal cells), since fibroblasts are susceptible to CHIKV infection following mosquito bite. Dermal fibroblasts induce the activation of innate immune responses such as IFNβ secretion, this has been described in HFF-1, HDF cell lines infected with dengue and Zika arboviruses [28][29][30] and in HT-1080 and HS 633T infected with CHIKV [31]. When treated with 100 μM NCAO, a decrease in viral replication was observed at 48 hpi (Figure 7), like what was observed in Vero and C6/36 cells.…”
Section: Discussionsupporting
confidence: 66%
“…Use of a full-length live attenuated DENV3 vaccine that induces B and T cell immune responses similar to those from natural infection facilitates the safe modeling of enhancement and protection [ 34 , 51 ]. Recent work suggests that the mechanism of attenuation of the TV003 monovalent vaccine components is increased sensitivity of the virus strain to type I interferon signaling, and this form of attenuation is also observed in clinical isolates [ 52 , 53 ]. Thus, markers associated with risk and protection will likely reflect those in natural infection.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have also shown that the ability to efficiently antagonize the IFN response confers an important selective advantage to flaviviruses. There is therefore a correlation between the IFN resistance of a given virus and its replication efficiency, pathogenicity and/or epidemiological fitness (Keller et al, 2006;Manokaran et al, 2015;Xia et al, 2018;Castro-Jiménez et al, 2022).…”
Section: Ifn and Flaviviruses: From In Vitro Data To In Vivo Outcomesmentioning
confidence: 99%